Preparation method of honeycomb ozone decomposition catalyst
By using special paper honeycombs made of glass fiber and wood pulp as a support, the catalytic material is supported and the dispersant is added to the catalyst pulp, the problem of catalyst activity loss in the prior art is solved, and an efficient and environmentally friendly ozone decomposition effect is achieved. .
Patent Information
- Application Number
- CN202411472420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
AI Technical Summary
When existing ozone decomposition catalysts prevent catalytic material from falling off, they need to add binders, resulting in loss of catalytic material activity and reduced catalytic efficiency.
Special paper honeycombs made of glass fiber and wood pulp are used as support to support the catalytic material, and dispersants are added to the catalyst pulp to evenly disperse the catalyst and avoid the use of binder.
It achieves efficient ozone decomposition, high catalyst adhesion strength, avoids loss of active sites, simple process, low cost and environmentally friendly.
Smart Images

Figure CN119425701A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy conservation and environmental protection, and particularly relates to a method for preparing a honeycomb ozone decomposition catalyst. Background Art
[0002] Ozone is an allotrope of oxygen with strong oxidizing and bactericidal properties. It forms a strong oxidizing group - hydroxyl radical in water, which can quickly remove organic pollutants in wastewater and decompose into oxygen. It is widely used in industrial waste gas treatment, removal of organic pollutants in wastewater, food processing and storage, sterilization of medical laboratories, household and commercial air purification and other fields. Atmospheric ozone (O3) from nature and humans is also an important pollutant. People will cough, have difficulty breathing and decreased lung function if they are active in an ozone environment of 320μg / m3 for 1 hour. Ozone can also participate in the reaction of unsaturated fatty acids, amino groups and other proteins in organisms, causing fatigue, coughing, chest tightness and chest pain in people who are directly exposed to high concentrations of ozone for a long time. Ozone can also make plant leaves turn yellow or even wither, causing damage to plants, and even causing a reduction in the yield of agricultural and forestry plants and a decline in economic benefits. It can also cause dye fading, discoloration of photo image layers, and aging of tires. Therefore, it is crucial to reduce ozone pollution and protect human health and environmental safety.
[0003] Common methods for eliminating ozone include adsorption, thermal decomposition, condensation, and catalytic decomposition. Relatively speaking, the catalytic decomposition method uses oxygen vacancies or hydroxyl groups on the surface of the catalytic material to decompose ozone into oxygen. It is carried out at room temperature and pressure without providing additional heat or light, and can meet the requirements of high decomposition rate, long-term stability, safety, and economy. The main component of the ozone decomposition catalyst is a carrier material containing a metal catalyst; usually alumina or silica is the main body. Common filter screens (ceramic honeycomb, aluminum honeycomb, pp honeycomb) as carriers of honeycomb-loaded catalytic materials have the advantage of low wind resistance. However, in order to prevent the problem of catalytic material falling off, a binder must be added, which causes the catalyst to be wrapped to a certain extent, resulting in a loss of activity of the catalytic material and a decrease in catalytic efficiency. Therefore, finding suitable catalyst materials and carriers is crucial to the effective catalytic decomposition of ozone. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a honeycomb ozone decomposition catalyst in view of the above technical problems, using a special paper honeycomb made of glass fiber and wood pulp as a carrier to load the catalytic material without adding a binder, thereby obtaining an ozone decomposition catalyst with high catalytic efficiency.
[0005] The method for preparing the honeycomb ozone decomposition catalyst in the technical solution of the present invention comprises the following steps: (1) Mixing glass fiber and wood pulp to obtain special paper honeycomb; (2) adding a dispersant to a catalyst slurry to obtain a catalyst slurry; (3) Coat the catalyst slurry on the paper honeycomb, blow it and dry it.
[0006] The wood pulp in the special paper honeycomb can improve the softness and formability of the paper honeycomb, and the glass fiber can improve the water resistance of the paper honeycomb, providing a carrier with good performance for the ozone decomposition catalyst; and a dispersant is added to the catalyst slurry to make the catalyst in the slurry evenly dispersed and can be evenly coated on the paper honeycomb, finally obtaining an ozone decomposition catalyst with excellent performance.
[0007] Furthermore, in step (1), the mass ratio of wood pulp to glass fiber is 5-15:1.
[0008] Furthermore, the glass fiber is pre-treated by mixing with a surfactant in an amount of 1.0 to 5.0 times its mass to improve the hydrophilicity of the glass fiber; the surfactant includes but is not limited to one or more of potassium laurate, sodium lauryl sulfate, sodium alkylbenzene sulfonate, and polyethylene glycol.
[0009] Furthermore, the catalyst is one or more of platinum, palladium, copper oxide, manganese oxide, cobalt oxide, nickel oxide, vanadium oxide, hydrotalcite, and hydrotalcite-like substances.
[0010] Furthermore, in step (2), the catalyst slurry is obtained by grinding the catalyst and water at a solid content of 10-40%.
[0011] Furthermore, the catalyst slurry is adjusted to a solid content of 5-20% with water before adding the dispersant.
[0012] Furthermore, the particle size of the catalyst in the catalyst slurry in step (2) is 600-1500 mesh.
[0013] Furthermore, in step (2), the mass of the dispersant is 2-5% of the mass of the catalyst slurry.
[0014] Preferably, the dispersant includes, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, ethyl cellulose, and hydroxypropyl methyl cellulose.
[0015] Furthermore, in step (3), the loading amount of catalyst slurry per unit volume of paper honeycomb is 30-40 g / L.
[0016] Furthermore, in step (3), the drying is performed by pre-drying at 50-80°C for 1-5h, and then rapid drying at 100-150°C for 0.5-2h.
[0017] Preferably, in step (3), the catalyst slurry is dip-coated or spray-coated on the paper honeycomb.
[0018] The present invention also provides a honeycomb ozone decomposition catalyst, which is prepared by the preparation method of the honeycomb ozone decomposition catalyst.
[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) The present invention uses a special paper honeycomb made of glass fiber and wood pulp as a carrier to load the catalytic material, thereby obtaining a honeycomb ozone decomposition catalyst with high decomposition efficiency, no secondary pollution and high applicability; (2) Wood pulp in special paper honeycombs can improve the softness and formability of paper honeycombs, and glass fiber can improve the water resistance of paper honeycombs, providing a carrier with good performance for ozone decomposition catalysts; (3) Adding a dispersant to the catalyst slurry makes the catalyst in the slurry evenly dispersed and can be evenly coated on the paper honeycomb, which helps to obtain an ozone decomposition catalyst with excellent performance; (4) The preparation method of the honeycomb ozone decomposition catalyst does not require any binder, has a simple process, low cost and is environmentally friendly, and can also avoid the loss of catalyst active sites; (5) The obtained honeycomb ozone decomposition catalyst material has high adhesion strength, does not fall off, is easy to clean, and is water-resistant and high-temperature resistant. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is an optical picture of the honeycomb ozone decomposition catalyst obtained in Example 1; Figure 2 This is an optical picture of the special paper honeycomb obtained in Example 1; Figure 3 The diagram is a diagram showing the decomposition effect of the honeycomb ozone decomposition catalyst obtained in Example 1 and Comparative Example 3 on low concentration ozone; Figure 4 This is a diagram showing the decomposition effect of the honeycomb ozone decomposition catalyst obtained in Example 1 on high concentration ozone. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below by specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not used for specific limitations of the present invention. And the accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If there is no special explanation, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0022] Embodiment 1:
[0023] The preparation method of the honeycomb ozone decomposition catalyst of this embodiment comprises the following steps: (1) Pre-treating glass fiber with sodium lauryl sulfate in an amount 1.0 times its mass. After pre-treating, wood pulp and glass fiber are mixed in a mass ratio of 8:1 to obtain a special paper honeycomb, such as Figure 2 As shown; (2) mixing a nickel-iron hydrotalcite catalyst with water at a solid content of 20% and then wet-grinding the mixture to obtain a catalyst stock slurry having a nickel-iron hydrotalcite particle size of 800 mesh; adjusting the catalyst stock slurry to a solid content of 10% with water; and adding 3.0% polyvinyl alcohol by weight of the catalyst stock slurry and mixing the mixture evenly to obtain a catalyst slurry; (3) The catalyst slurry was dip-coated on the paper honeycomb at a loading rate of 30 g / L per unit volume of the paper honeycomb, and the excess slurry in the honeycomb pores was purged and pre-dried at 60°C for 2 h, and then rapidly dried at 120°C for 1.0 h. The honeycomb ozone decomposition catalyst was obtained as shown in FIG. Figure 1 As shown, it can be seen that the catalyst is evenly attached to the gaps in the glass fiber.
[0024] Figure 3-4 It can be seen that the obtained honeycomb ozone decomposition catalyst has a good catalytic decomposition effect regardless of whether it is in an environment of low ozone concentration or high ozone concentration.
[0025] Embodiment 2:
[0026] The preparation method of the honeycomb ozone decomposition catalyst of this embodiment comprises the following steps: (1) Pre-treating the glass fiber by mixing it with polyethylene glycol in an amount 1.5 times its mass, and mixing the wood pulp and the glass fiber in a mass ratio of 8:1 to obtain a special paper honeycomb; (2) mixing a manganese oxide catalyst with water at a solid content of 25% and then wet grinding the mixture to obtain a catalyst stock slurry having a manganese oxide particle size of 900 meshes, adjusting the catalyst stock slurry to a solid content of 15% with water, and adding ethyl cellulose in an amount of 3.5% by weight of the catalyst stock slurry and mixing the mixture evenly to obtain a catalyst slurry; (3) The catalyst slurry was sprayed on the paper honeycomb at a loading rate of 30 g / L per unit volume of the paper honeycomb, and the excess slurry in the honeycomb pores was purged and pre-dried at 65° C. for 2 h, and then rapidly dried at 130° C. for 1.0 h.
[0027] Embodiment 3:
[0028] The preparation method of the honeycomb ozone decomposition catalyst of this embodiment comprises the following steps: (1) Pre-treating glass fiber by mixing it with sodium alkylbenzene sulfonate in an amount 2.0 times its mass, and mixing the wood pulp and glass fiber in a mass ratio of 8:1 to obtain a special paper honeycomb; (2) mixing a nickel-iron hydrotalcite catalyst with water at a solid content of 30% and then wet-grinding the mixture to obtain a catalyst stock slurry having a nickel-iron hydrotalcite particle size of 1000 mesh; adjusting the catalyst stock slurry to a solid content of 20% with water; and adding 4.0% polyvinyl alcohol by weight of the catalyst stock slurry and mixing the mixture evenly to obtain a catalyst slurry; (3) The catalyst slurry was dip-coated on the paper honeycomb at a loading rate of 30 g / L per unit volume of the paper honeycomb, and the excess slurry in the honeycomb pores was purged and pre-dried at 70° C. for 2 h, and then rapidly dried at 140° C. for 1.0 h.
[0029] Embodiment 4:
[0030] The difference between this embodiment and embodiment 1 is that in step (1), the glass fiber is mixed with sodium lauryl sulfate in an amount 1.0 times the mass of the glass fiber for pretreatment, and after the pretreatment, the wood pulp and the glass fiber are mixed in a mass ratio of 10:1 to obtain a special paper honeycomb.
[0031] Embodiment 5:
[0032] The difference between this embodiment and embodiment 1 is that in step (1), the glass fiber is mixed with 1.0 times the mass of sodium lauryl sulfate for pretreatment, and after the pretreatment, the wood pulp and the glass fiber are mixed in a mass ratio of 12:1 to obtain a special paper honeycomb.
[0033] Embodiment 6:
[0034] The difference between this embodiment and embodiment 1 is that in step (1), the glass fiber is mixed with sodium lauryl sulfate in an amount 1.0 times its mass for pretreatment, and after the pretreatment, the wood pulp and the glass fiber are mixed in a mass ratio of 3:1 to obtain a special paper honeycomb.
[0035] Embodiment 7:
[0036] The difference between this embodiment and embodiment 1 is that in step (1), the glass fiber is mixed with 1.0 times the mass of sodium lauryl sulfate for pretreatment, and after the pretreatment, the wood pulp and the glass fiber are mixed in a mass ratio of 12:1 to obtain a special paper honeycomb.
[0037] Embodiment 8:
[0038] The difference between this embodiment and embodiment 1 is that in step (3), the catalyst slurry is dip-coated on the paper honeycomb in an amount of 35 g / L of catalyst slurry per unit volume of the paper honeycomb, excess slurry in the honeycomb pores is blown away, and the paper honeycomb is pre-dried at 60° C. for 2 h, and then quickly dried at 120° C. for 1.0 h.
[0039] Embodiment 9:
[0040] The difference between this embodiment and embodiment 1 is that in step (3), the catalyst slurry is dip-coated on the paper honeycomb in an amount of 40 g / L of catalyst slurry per unit volume of the paper honeycomb, excess slurry in the honeycomb pores is blown away, and the paper honeycomb is pre-dried at 60° C. for 2 h, and then quickly dried at 120° C. for 1.0 h.
[0041] Embodiment 10:
[0042] The difference between this embodiment and embodiment 1 is that in step (3), the catalyst slurry is dip-coated on the paper honeycomb in an amount of 25 g / L of catalyst slurry per unit volume of the paper honeycomb, excess slurry in the honeycomb pores is blown away, and the paper honeycomb is pre-dried at 60° C. for 2 h, and then quickly dried at 120° C. for 1.0 h.
[0043] Embodiment 11:
[0044] The difference between this embodiment and embodiment 1 is that in step (3), the catalyst slurry is dip-coated on the paper honeycomb in an amount of 45 g / L of catalyst slurry per unit volume of the paper honeycomb, excess slurry in the honeycomb pores is blown away, and the paper honeycomb is pre-dried at 60° C. for 2 h, and then quickly dried at 120° C. for 1.0 h.
[0045] Comparative Example 1 The preparation method of the honeycomb ozone decomposition catalyst of this comparative example comprises the following steps: (1) mixing a nickel-iron hydrotalcite catalyst with a solid content of 20% and then wet-grinding the mixture to obtain a catalyst stock slurry having a nickel-iron hydrotalcite particle size of 800 mesh, adjusting the catalyst stock slurry to a solid content of 10%, and adding 3.0% polyvinyl alcohol by weight of the catalyst stock slurry and mixing the mixture to obtain a catalyst slurry; (2) The catalyst slurry was dip-coated on the paper honeycomb at a loading rate of 30 g / L per unit volume of the paper honeycomb, and the excess slurry in the honeycomb pores was purged and pre-dried at 60° C. for 2 h, and then rapidly dried at 120° C. for 1.0 h.
[0046] Comparative Example 2 The preparation method of the honeycomb ozone decomposition catalyst of this comparative example comprises the following steps: (1) mixing a nickel-iron hydrotalcite catalyst with a solid content of 20% and then wet-grinding the mixture to obtain a catalyst stock slurry having a nickel-iron hydrotalcite particle size of 800 mesh, adjusting the catalyst stock slurry to a solid content of 10%, and adding 3.0% polyvinyl alcohol by weight of the catalyst stock slurry and mixing the mixture to obtain a catalyst slurry; (2) The catalyst slurry was coated on the wood pulp at a loading rate of 30 g / L per unit volume of wood pulp, and the excess slurry in the wood pulp pores was blown away. The wood pulp was pre-dried at 60°C for 2 h, and then rapidly dried at 120°C for 1.0 h.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that in step (2), the nickel-iron hydrotalcite catalyst is mixed with water at a solid content of 20% and then wet-ground to obtain a catalyst slurry with a nickel-iron hydrotalcite particle size of 800 mesh, and then the catalyst slurry is adjusted to a solid content of 10% with water, and 3.0% of polyvinyl alcohol by weight of the catalyst slurry and 10.0% of acrylic resin binder by weight of the catalyst slurry are added and mixed evenly to obtain a catalyst slurry.
[0048] The adhesion strength test of the ozone decomposition catalyst obtained in the above embodiments and comparative examples was carried out. The test method was as follows: 2.5 L of water was placed in a 5 L beaker, and the coated module with a specification of length × width × thickness = 30 × 30 × 10 mm was placed in the water. The module was stirred at a magnetic stirring speed of 300 rpm for 1 hour. After being fully dried, the weight change of the module was measured (dried at 110 ° C for 10, 12, and 14 hours, and the weight remained unchanged for three times, which was considered fully dried), and the powder removal rate was calculated.
[0049] In Examples 1-5 and 8-9, a special paper honeycomb made of glass fiber and wood pulp is used as a carrier to load a catalytic material, and a honeycomb ozone decomposition catalyst with high decomposition efficiency, no secondary pollution, and high applicability is obtained, and the catalyst shedding rate is less than 1%; Example 6 uses less wood pulp and more glass fiber, and the obtained special paper honeycomb has a larger hardness, reduced flexibility, and poorer molding performance; Example 7 uses more wood pulp and less glass fiber, and the obtained special paper honeycomb has lower mechanical strength and poorer durability; Example 10 has less catalyst loaded on the unit volume of paper honeycomb, the catalyst shedding rate is 0.8%, and the catalytic decomposition efficiency is significantly reduced; Example 11 has more catalyst loaded on the unit volume of paper honeycomb, and the special The pores of paper honeycombs are easily blocked, and the catalyst is also easy to fall off, with a shedding rate of 5%, resulting in a decrease in the catalytic decomposition efficiency of the ozone decomposition catalyst; in Comparative Example 1, commercially available paper honeycombs are used as carriers to load the catalyst, which will foam and deform when exposed to water, resulting in the catalyst falling off, with a shedding rate of 10%, and the strength is low, and the resulting ozone decomposition catalyst has a low catalytic decomposition efficiency; in Comparative Example 2, the catalyst is directly dipped on wood pulp, and the wood pulp has a low strength. The dipped catalyst will soften and deform due to excessive humidity, resulting in a large amount of catalyst falling off, with a shedding rate of 30%, and the resulting ozone decomposition catalyst has a low catalytic decomposition efficiency; in Comparative Example 3, a binder is added to the catalyst slurry, resulting in part of the catalyst being wrapped by the binder, resulting in a loss of active sites, causing a decrease in catalytic decomposition efficiency, such as Figure 3 As shown, the catalyst shedding rate is 0.8%.
[0050] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A method for preparing a honeycomb ozone decomposition catalyst, characterized in that: The following steps are involved: (1) Mixing glass fiber and wood pulp to obtain special paper honeycomb; (2) adding a dispersant to a catalyst slurry to obtain a catalyst slurry; (3) Coat the catalyst slurry on the paper honeycomb, blow it and dry it.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of glass fiber to wood pulp is 5-15:
1.
3. The preparation method according to claim 1 or 2, characterized in that: The glass fiber is pre-treated by mixing with a surfactant in an amount of 1.0 to 5.0 times its mass.
4. The preparation method according to claim 1, characterized in that: In step (2), the catalyst slurry is obtained by grinding the catalyst and water at a solid content of 10-40%.
5. The preparation method according to claim 4, characterized in that: The catalyst is one or more of platinum, palladium, copper oxide, manganese oxide, cobalt oxide, nickel oxide, vanadium oxide, hydrotalcite, and hydrotalcite-like substances.
6. The preparation method according to claim 1, characterized in that: The particle size of the catalyst in the catalyst slurry of step (2) is 600-1500 mesh.
7. The preparation method according to claim 1, characterized in that: The mass of the dispersant in step (2) is 2-5% of the mass of the catalyst slurry.
8. The preparation method according to claim 1, characterized in that: In step (3), the loading amount of catalyst slurry per unit volume of paper honeycomb is 30-40 g / L.
9. The preparation method according to claim 1, characterized in that: The drying in step (3) is pre-drying at 50-80°C for 1-5h, and then rapid drying at 100-150°C for 0.5-2h.
10. A honeycomb ozone decomposition catalyst, characterized in that: The method is prepared according to claim 1.